Pengembangan Media Pembelajaran Interaktif Bahasa Arab Berbasis Autoplay Media Studio dengan Model ADDIE pada Peserta Didik Kelas VIII SMP - Asmarita Asmarita; Yeni Nuriah Fitri (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aimed to develop Autoplay Media Studio-based interactive multimedia for Arabic language learning using the ADDIE model for eighth-grade students at SMP Ahmad Dahlan Jambi City and to examine its validity, practicality, and user acceptance. The study employed a Research and Development (R&D) method through the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of one material expert, one media expert, one Arabic language teacher, and 26 eighth-grade students. Data were collected through observations, interviews, questionnaires, tests, and documentation and analyzed using descriptive statistics. The findings showed that the material expert validation reached 83.33%, media expert validation 80.00%, and teacher practicality assessment 93.33%, all categorized as excellent. The implementation involving 26 students produced a total score of 1,736 out of a maximum score of 1,950, with a mean score of 4.45 and a response percentage of 89.03%, indicating an excellent category. The evaluation stage confirmed that continuous improvements throughout the ADDIE process produced a systematic, practical, and user-friendly learning medium. Therefore, the developed Autoplay Media Studio-based interactive multimedia is feasible for supporting Arabic language learning at the junior secondary school level.